Bearing capacity of strip footing on reinforced layered granular soils - Cicek, Elif; Guler, Erol (Journal of Civil Engineering and Management, 2015)
In this study a limit equilibrium method is proposed to determine the bearing capacity of strip foundations on geosynthetic reinforced sand soils. A two-layered granular soil was foreseen to represent the loose in situ soil and the compacted fill above the reinforcement. First the modified bearing capacity factors Nq and Nγ were derived for the two layered granular reinforced soil. The bearing capacities were also calculated for different reinforcement geometries and soil properties using Finite Element analyses. The bearing capacities obtained from Finite Element and Limit Equilibrium analyses were compared, it was seen a good agreement. Therefore, it was concluded that the new limit equilibrium method proposed in this paper for reinforced two-layered soils can be successfully used in calculating the bearing capacities of geosynthetic reinforced soils.